Simulation Study on Single-Event Burnout Reliability of 900V 4H-SiC Quasi Vertical Double Diffused MOSFET - Jin-Ke Shi; Ying Wang; Xin-Xing Fei; Biao Sun; Yan-Xing Song; Yu-Qian Liu; Wei Zhang (IEEE Access)
In this work, the single-event burnout (SEB) performance and reasons of the proposed 900V SiC quasi-vertical double diffusion MOSFET with deepened drain (T-QVDMOSFET) are analyzed from the spatial distribution of physical quantities such as power density, lattice temperature and total current density by 2-D numerical simulation, and a SEB-hardened structure (TB-QVDMOSFET) with buried oxygen layer (BOX) and heavily doped N-type current expansion layer (CSL) inside the device is proposed. Simulation results indicate that when heavy-ion with linear energy transfer (LET) of 0.5pC/ $μ $ m strikes the device, the primary cause of SEB in the SiC T-QVDMOSFET is the high transient current density and electric field at the trench gate corner. This phenomenon leads to increased power dissipation, resulting in excessive temperatures that ultimately cause thermal failure. The BOX and a heavily doped N-type CSL added in the SEB-hardened structure change the current flow path, and the transient current concentrated in the region is dispersed. This modification reduces the high current density and power dissipation at the trench corner, thereby significantly enhancing the device’s resistance to SEB. Compared to the original device, the SEB threshold voltage is increased from 270V to 478V, marking a 77% improvement.